Characterization of Zn-Doped MgTiO3 Powders Synthesized by Dissolved Metals Mixing Method - Musyarofah, Musyarofah; Tanaka, Isao; Mohamed, Zakiah; Poo-arporn, Yingyot; Ernawati, Lusi; Yudoyono, Gatut; Prayitno, Budi (Universitas Gadjah Mada, 2025)
Zn-doped magnesium titanate powders with different Zn compositions, x = 0 to 1, were synthesized using the dissolved metals mixing method. The roles of calcination temperature and dopant Zn composition on powder morphology, phase composition, crystallite size, crystalline cell volume, and local environment were investigated through scanning electron microscope (SEM) observation, Rietveld analysis of powder X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and X-ray absorption spectroscopy (XAS) for Ti K-edge X-ray absorption near edge structures (XANES). We found that the geikielite solid solutions were formed during the pre-calcination at 400 °C for 1 h. Results show spherical particles ( 1 µm) with minimal size variation across calcination temperatures (600–800 °C) and Zn compositions, though some agglomeration occurs. After calcination at 600 °C for 4 h, the crystalline cell volume of geikielite was proportional to the Zn composition, implying the formation of the solid solution in the range of Zn composition up to the level close to x = 1. This successful synthesis of the Zn-doped magnesium titanate nanocrystals at temperatures much lower than those required by the solid-state reaction method was thereby well demonstrated.